(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2024)
The use of additives and addictive substances in various foods, drinks, and other consumer products is increasing along with the times. This PkM activity aims to provide students with an understanding of additives and addictive substances and the side effects they cause through educational activities assisted by animation media. This activity was held at SDN 2 Labalawa and attended by 28 class V students, consisting of 16 male students and 12 female students. The results of the PkM activities showed that 22 students (79%) had a good understanding of the material presented, 4 students (14%) were in the sufficient category, and 2 students (7%) were in the poor category. These results show that the majority of participants have a good understanding of additives and addictive substances and the side effects they cause. Education regarding additives and addictive substances is essential, given the increasing variety of products offered by companies, so that consumers can sort and choose well the goods they will consume. Overall, PkM activities were doing well in accordance with the stated objectives